2016
DOI: 10.1080/02640414.2015.1136068
|View full text |Cite
|
Sign up to set email alerts
|

Timescales for exploratory tactical behaviour in football small-sided games

Abstract: The aim of this study was to identify the dynamics of tactical behaviour emerging on different timescales in football small-sided games and to quantify short- and long-term exploratory behaviour according to the number of opponents. Two teams of four professional male footballers played small-sided games against two different teams with a variable number of opponents (3, 5 and 7). Data were collected using a combination of systematic observation and a non-differential global positioning system (15 Hz). The tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
103
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 37 publications
3
103
0
5
Order By: Relevance
“…Six articles used FUTSAT (26,29,30,34,36,38), 14 articles used polar coordinates (12, 21-23, 27-30, 33, 37, 42-44), and five articles used technicaltactical video analysis (7,20,35,(39)(40)(41). For this review, it should be noted that 3.1 Effect of pitch dimension manipulation Table 2 presents the results of articles that analyzed the effect of manipulation of pitch dimensions.…”
Section: Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…Six articles used FUTSAT (26,29,30,34,36,38), 14 articles used polar coordinates (12, 21-23, 27-30, 33, 37, 42-44), and five articles used technicaltactical video analysis (7,20,35,(39)(40)(41). For this review, it should be noted that 3.1 Effect of pitch dimension manipulation Table 2 presents the results of articles that analyzed the effect of manipulation of pitch dimensions.…”
Section: Screeningmentioning
confidence: 99%
“…However, when technical tactical actions were analyzed, no significant differences were observed (29). One study showed that the team with numerical superiority performed more defensive tactical behaviours, and the team with numerical inferiority performed a greater number of penetrations of the defensive line or movements of the player with the ball towards the goal area (30).…”
Section: Screeningmentioning
confidence: 99%
See 3 more Smart Citations